Kolonialisme, Perekrutan Militer, dan Transformasi Sosial: Pengaruh Belanda di Minahasa - Andani, Devi; Saefudin, Arif (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The Dutch came to Minahasa land to exploit the fertile Minahasa land with various natural resources, but there was a pattern of social change that occurred between the Dutch who were successful in "making friends" with the Minahasa people. This slowly changed the structure of Minahasa society. So Minahasa is an area famous for having the largest and longest Dutch influence in Indonesian history. This article uses library research methods related to critical historical methods. The steps in this research are associated with using historical research methods which include :heuristics, criticism, interpretation and historiography. The Dutch saw a lot of instability and rebellion in several areas that occurred in controlling the Dutch East Indies government and took the initiative to recruit military members again in a more intensive and selective way. The recruitment process for Dutch East Indies military members carried out in Minahasa was not followed by a rejection process. The presence of the Dutch in the lives of the Minahasan people created stereotypes for the people during colonialism. This certainly creates a paradigm for people's thinking during colonialism. The results of the reconstruction of the thoughts of the Minahasa people who had united with the Dutch certainly gave rise to resistance and disagreement regarding this friendly relationship.